Being a Small State: Discussion on the Role of Size - Lingevičius, Justinas (Baltic Journal of Political Science, 2018)
This paper discusses theoretical debates regarding small states and their foreign policy and also argues that research should include more analysis of small states’ identities and the dominant meanings related to being a small state. Using poststructuralistic theoretical perspective and discourse analysis, two empirical cases – Lithuania and New Zealand – are analysed with attention paid to the meanings of smallness and the ways these meanings are constructed. Empirical analysis follows with suggestions for how future research of small states could be improved.
Keywords: Small state; discourse; poststructuralism; Lithuania; New Zealand; size